2007
DOI: 10.2465/gkk.36.1
|View full text |Cite
|
Sign up to set email alerts
|

Peridotite xenoliths from the Takeshima seamount, Japan: an insight into the upper mantle beneath the Sea of Japan

Abstract: The Sea of Japan is one of the back arc basins distributed around the western rim of the Pacific. Nature of the plume for back arc basin (= BAB) opening is unknown partly because petrological characteristics of the BAB mantle are not well known compared with mid ocean ridge (= MOR) mantle.Peridotite xenoliths in an alkali basalt dredged from the Takeshima seamount (tentative name), ca. 230 km to the north of Oki islands, are examined to clarify the petrological feature of the Japan Sea mantle. They are spinel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 46 publications
(28 reference statements)
3
15
0
Order By: Relevance
“…The flat to V -shaped KR375, KR202, and published clinopyroxene patterns are similar to clinopyroxene patterns of Type I Takeshima seamount xenoliths ( Fig. 2B; Ninomiya et al, 2007). The LREE enrichment cannot be explained by a simple partial melting event.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The flat to V -shaped KR375, KR202, and published clinopyroxene patterns are similar to clinopyroxene patterns of Type I Takeshima seamount xenoliths ( Fig. 2B; Ninomiya et al, 2007). The LREE enrichment cannot be explained by a simple partial melting event.…”
Section: Discussionsupporting
confidence: 51%
“…The clinopyroxene of the most fertile sample KR120 Ohara et al, 2002Ohara et al, , 2003, and Type I Takeshima seamount xenoliths (Ninomiya et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we report data for mantle xenolith localities within the Sea of Japan, one of the back-arc basins of the Western Pacific, including Oki-Dogo island, which has been interpreted as a remnant of continental lithosphere off the coast of Honshu (Takahashi, 1978a;Abe et al, 2003). Ninomiya et al (2007) reported peridotite xenoliths from a small seamount in the Sea of Japan.…”
Section: P E T Ro L O G I C a L S U M M A Ry O F P E R I D Ot I T E Xmentioning
confidence: 99%
“…The basalt sample contains peridotite xenoliths with variable size from a few millimetres to usually < 3cm (up to 10 10 cm) and their-derived xenocrysts (Ninomiya et al, 2007). The basalt sample shows porphyritic texture.…”
Section: Geological Background and Sample Descriptionmentioning
confidence: 99%
“…A basaltic block containing peridotite xenoliths was dredged from the Seifu Seamount (Ninomiya et al, 2007), located at northeast of the Tsushima Basin in the southwest Japan Sea (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%